Light-transmitting tea fiber modified polypropylene composite material for automotive trim and preparation method of light-transmitting tea fiber modified polypropylene composite material
By using specific formulas and processing techniques of translucent polypropylene and modified tea fibers in automotive interior materials, the problem of difficulty in filling tea fibers in existing materials at high temperatures is solved, the combination of translucent and tea fiber appearance is achieved, and the odor level of the material is improved, providing new possibilities for automotive interior design.
Patent Information
- Application Number
- CN202411978044.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Existing automotive interior light-transparent materials are difficult to fill tea fibers when processing temperatures are high, resulting in difficult to achieve the appearance design of transparent tea fibers, and the odor level of the material is insufficient.
Light-transmitted polypropylene (PP) is used as the substrate, and through specific formulations and processing processes, including the use of homopolypolypropylene, random copolymer polypropylene, whiskers, SEBS, antioxidants, compatible agents, anti-UV agents, lubricants and modified tea fibers, ensuring that the material maintains light-transmitting and the special appearance of tea fibers at lower processing temperatures, while using the tea aroma of tea fibers to enhance the odor grade of the material.
The production of translucent tea fiber modified polypropylene composite material at lower processing temperatures is realized, showing the special appearance of tea fibers, and improving the odor level of the material, providing a new automotive interior design idea.
Smart Images

Figure CN119752031A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a light-transmitting tea fiber modified polypropylene composite material for automobile interior decoration. The obtained material has the characteristics of light transmission, special tea fiber appearance, high strength and the like, and belongs to the technical field of polymer material processing and modification. Background Art
[0002] The development of new energy vehicles has brought about a new trend in automobile exterior design, and the light transmittance of composite materials has become an indicator that needs attention. On parts such as exterior bumpers and interior trim panels, by designing patterns or patterns and placing backlight components on the back, the parts can be made decorative, which requires the material to have a high light transmittance and a good light diffusion effect. For example, publication number CN118478818A proposes a light-transmitting bumper, a vehicle, and a light-transmitting bumper production process. The patent details the application method of existing light-transmitting polypropylene materials on automobile bumpers; publication number CN215042562U introduces a light-transmitting automobile interior panel part, the light source system of which requires a small space, can be used in more occasions, and has a higher degree of design freedom; in summary, light-transmitting materials already have broad application prospects and space in the automotive industry.
[0003] At present, the main transparent plastics for automobile interiors are polycarbonate PC, because PC has a very high light transmittance, and the transmittance of visible light can reach more than 90%, which is comparable to glass. However, considering the cost of materials and the difficulty of processing, transparent PP has gradually emerged this year. Compared with PC, the transmittance of transparent PP can reach up to 70%, and the material cost is only 50-60% of PC. In addition, since the processing temperature of PC is 30-50℃ higher than that of PP, it usually requires a processing temperature of about 250℃, and the decomposition temperature of tea fiber is about 200℃, which makes it difficult to fill tea fiber into the composite material. Therefore, in order to achieve the appearance design of transparent tea fiber, a lower processing temperature must be used. Therefore, transparent PP is obviously more suitable for addition. For example: Publication No. CN118085458A introduces a high-content tea fiber-filled polypropylene composite material, in which the total addition of tea fiber reaches 25%. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a light-transmitting tea fiber modified polypropylene composite material for automobile interior and a preparation method thereof. The obtained material uses the transparent characteristics of light-transmitting polypropylene to show the appearance of tea fiber to achieve the special appearance effect of plant fiber; on the other hand, because the tea fragrance of tea fiber itself is a pleasant fragrance, making full use of this advantage can improve the odor level of the composite material.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A light-transmitting tea fiber modified polypropylene composite material for automobile interior, characterized in that it is made of raw materials containing the following parts by weight:
[0007] Homopolymer polypropylene 30-50 parts;
[0008] Random copolymer polypropylene 20-30 parts;
[0009] Whiskers 10-20 parts;
[0010] Styrene-ethylene-butylene-styrene copolymer (SEBS) 10-20 parts;
[0011] Antioxidant 0.1-2 parts;
[0012] Compatibilizer 0.1-1 part;
[0013] Anti-UV agent 0.1-2 parts;
[0014] Lubricant 0.1-0.5 parts;
[0015] 1-2 parts of tea fiber.
[0016] in,
[0017] The polypropylene material is one or more homopolymer polypropylenes, and the specific requirement is that the melt flow rate is between 20 and 100 g / 10 min at 230° C. and 2.16 kg.
[0018] The polypropylene material is one or more of random copolymer polypropylenes, and the specific requirement is that the melt flow rate is between 10 and 20 g / 10 min under the conditions of 230° C. and 2.16 kg.
[0019] The whiskers are one or more of basic magnesium sulfate whiskers and basic barium sulfate whiskers, with a length of 20 to 50 μm and a diameter of 2 to 5 μm.
[0020] The styrene-ethylene-butylene-styrene copolymer (hereinafter referred to as SEBS) is a linear structure, and the specific requirement is that the viscosity of a 10 mass % toluene solution at 25° C. is 400-600 cp.
[0021] The antioxidant comprises a primary antioxidant and a secondary antioxidant; the primary antioxidant is selected from hindered amines; the secondary antioxidant is a combination of one or more of phosphites, thiodipropionates and thiols.
[0022] The compatibilizer is maleic anhydride grafted polypropylene, and the effective grafting activity is above 3%. The specific requirement is that the melt flow rate is between 5 and 20 g / 10 min under the conditions of 230° C. and 2.16 kg.
[0023] The anti-UV agent is a compound of one or more of benzophenone, benzotriazole and hindered amine.
[0024] The lubricant is one or more of zinc stearate, magnesium stearate and calcium stearate.
[0025] The tea fiber is one or more of green tea fiber, black tea fiber and oolong tea fiber modified by silane coupling agent KH570, and the specific requirements are that the length is 1-10mm and the diameter is 20-100μm.
[0026] The preparation method of the above-mentioned light-transmitting tea fiber modified polypropylene composite material for automobile interior decoration comprises the following specific steps:
[0027] (1) mixing two types of polypropylene, a compatibilizer and an antioxidant and stirring them uniformly to obtain a mixture;
[0028] (2) adding the mixed material into the main feed port of the twin-screw extruder, adding the whisker, SEBS, lubricant and anti-UV agent into the side feed port 1#, and adding the tea fiber into the side feed port 2#;
[0029] (3) After the processing technology is set, melt blending, cooling, granulation, and drying are performed to obtain a light-transmitting tea fiber modified polypropylene composite material.
[0030] (4) The processing technology involved in step (3) is as follows: the processing temperatures of zones I to X of the twin-screw extruder are 125°C, 155°C, 165°C, 165°C, 170°C, 175°C, 180°C, 185°C, 185°C, 185°C. The main screw speed is 300-450r / min, the water tank temperature is 23°C-50°C, and the melt temperature should be controlled within 200°C; the side feed port 1# should be after the melting section and before the mixing section of the twin-screw extruder to prevent the whiskers from being subjected to excessive shearing and resulting in performance degradation; the side feed port 2# should be after the mixing section and before the metering section of the twin-screw extruder to prevent the tea fibers from being coked at high temperature and resulting in yellowing of the appearance;
[0031] The advantages of the present invention are:
[0032] 1. The high light transmittance of translucent PP is used to display the appearance of tea fiber to achieve the special appearance effect of plant fiber, and provide new design ideas for the translucent interior of automobiles.
[0033] 2. Improve the odor level of the composite material through the tea fragrance of the tea fiber itself.
[0034] 3. Through the adaptation of specific screw combination and feeding method, the aspect ratio of whiskers is retained to prevent the composite material from falling; the granularity of tea fiber is retained to prevent excessive shearing. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Example 1 sample appearance;
[0036] Figure 2 Example 4 sample appearance;
[0037] Figure 3 .Appearance of sample of comparative example 3. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below by way of examples and comparative examples, but the present invention is not limited to the scope of the examples.
[0039] In the composite material formulations of the embodiments and comparative examples:
[0040] Polypropylene A is homopolymer polypropylene with a melt flow rate of about 100g / 10min; polypropylene B is random copolymer polypropylene with a melt flow rate of about 10g / 10min; the whisker is basic magnesium sulfate whisker with a whisker length of 25±5μm; SEBS is a linear structure with a melt flow rate of about 5g / 10min; talcum powder has a particle size of 3000 mesh; POE is a 4C structural unit with a melt flow rate of about 2g / 10min; the additive package is a mixture of scratch-resistant additives, anti-UV additives, antioxidants, compatibilizers and lubricants; tea fiber A is green tea fiber powder with a particle size of 200-300μm; tea fiber B is oolong tea fiber powder with a particle size of 1-2mm;
[0041] In the composite material tests of the embodiments and comparative examples:
[0042] The bending modulus is tested according to the IS0178 standard, with a bending speed of 2mm / min; the simply supported beam notch impact is tested according to the IS0179 standard, with a test temperature of 23°C; the light transmittance is tested according to the GB / T 2410-2008 standard: Method B photometer method is selected, and the size of the test sample is 50mm*50mm*2.5mm.
[0043] Table 1 Material composition of Examples 1-5 (weight percentage)
[0044] Example 1 Example 2 Example 3 Example 4 Example 5 Polypropylene A 40 63 / 40 40 Polypropylene B 23 / 63 23 23 Whiskers 10 10 10 10 10 SEBS 25 25 25 25 25 Additive package 2 2 2 2 2 Tea Fiber A 0.5 0.5 0.5 2 0.5 Tea Fiber B 0.5 0.5 0.5 0.5 2
[0045] Table 2 Comparative Examples 1-3 Material Composition (Weight Percentage)
[0046]
[0047] Table 3 Material performance test results of Examples 1-5 and Comparative Examples 1-3
[0048]
[0049]
[0050]
[0051] From the material performance test results of Examples 1, 2, and 3, it can be seen that: ① The higher the content of random copolymer PP in the substrate, the higher the overall transmittance and haze of the composite material, and the better the transparency after being made into a sample. In addition, the content of random copolymer PP will also affect the notched impact strength and flexural modulus of the composite material. When its content increases, the notched impact strength of the material increases significantly, with an increase of 104.5%, and the flexural modulus is reduced by about 9.2% at this time; ② The higher the content of homopolymer PP in the substrate, the overall transmittance and haze of the composite material show a slight downward trend, while the flexural modulus of the material increases slightly by about 11.8%, and the notched impact strength decreases significantly by about 26.8%;
[0052] From the material performance test results of Examples 1, 4, and 5, it can be seen that: since the overall particle size of green tea fiber is smaller than that of oolong tea fiber, when both are added into the composite material, the effect of green tea fiber on the light transmittance of the composite material is significantly greater than that of oolong tea fiber, which affects the appearance of tea fiber in the composite resin, and the overall trend is unfavorable. Specifically, when the content of green tea fiber increases from 0.5 parts to 2 parts, the transmittance of the composite material loses 24.7% and the haze increases by 13.6%. In addition, after the content of tea fiber is increased, the overall smell tends to deteriorate, and the flavor of Example 4 also changes from a single tea fragrance to two flavors of tea fragrance + paste.
[0053] From the results of the material performance tests of Examples 1, 2, 3 and Comparative Example 1, it can be seen that the overall performance of the light-transmitting tea fiber PP formula has basically reached the requirements of traditional PP interior panels, among which the performance indicators of Example 3 are the closest, and the smell has also changed from the burnt smell of plastic to the fragrance of tea.
[0054] From the results of the material performance tests of Examples 1, 2, 3 and Comparative Example 2, it can be seen that the addition of tea fibers will significantly reduce the transmittance of the light-transmitting PP and significantly increase its haze. This is because the two types of tea fibers themselves are not light-transmitting, which in turn affects the overall light-transmitting performance of the composite material.
[0055] From the results of the performance tests of Examples 1, 2, 3 and Comparative Example 3, it can be seen that the mechanical properties of the light-transmitting tea fiber PP material and the traditional tea fiber PP interior material are similar, but the odor level, flavor type and light transmittance of the light-transmitting tea fiber PP material are obviously more advantageous. The improvement of these properties can provide better design space for automotive interior design experts to a great extent.
Claims
1. A light-transmitting tea fiber modified polypropylene composite material for automobile interior, characterized in that: Made from the following raw materials in parts by weight: Homopolymer polypropylene 30-50 parts; Random copolymer polypropylene 20-30 parts; Whiskers 10-20 parts; Styrene-ethylene-butylene-styrene copolymer (SEBS) 10-20 parts; Antioxidant 0.1-2 parts; Compatibilizer 0.1-1 part; Anti-UV agent 0.1-2 parts; Lubricant 0.1-0.5 parts; 1-2 parts of tea fiber.
2. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The polypropylene material is one or more homopolymer polypropylenes, and the melt flow rate is between 20 and 100 g / 10 min at 230° C. and 2.16 kg.
3. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The polypropylene material is one or more random copolymer polypropylenes, and the melt flow rate is between 10 and 20 g / 10 min at 230° C. and 2.16 kg.
4. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The whiskers are one or more of basic magnesium sulfate whiskers and basic barium sulfate whiskers, with a length of 20 to 50 μm and a diameter of 2 to 5 μm.
5. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The styrene-ethylene-butylene-styrene copolymer has a linear structure, and the specific requirement is that the viscosity of a 10 mass % toluene solution at 25° C. is 400-600 cp.
6. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and a secondary antioxidant; the primary antioxidant is selected from hindered amines; the secondary antioxidant is a combination of one or more of phosphites, thiodipropionates and thiols.
7. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene, and the effective grafting activity is above 3%; the flow rate of the melt is between 5 and 20 g / 10 min under the conditions of 230° C. and 2.16 kg.
8. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The anti-UV agent is a compound of one or more of benzophenone, benzotriazole and hindered amine.
9. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The lubricant is one or more of zinc stearate, magnesium stearate and calcium stearate.
10. The light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 1, characterized in that: The tea fiber is one or more of green tea fiber, black tea fiber and oolong tea fiber modified by silane coupling agent KH570, and the specific requirements are that the length is 1-10mm and the diameter is 20-100μm.
11. A method for preparing a light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to any one of claims 1 to 10, characterized in that: The following steps are involved: Step 1, mixing two types of polypropylene, a compatibilizer and an antioxidant and stirring them uniformly to obtain a mixture; Step 2: Add the mixed material into the main feed port of the twin-screw extruder, add the whisker, SEBS, lubricant and anti-UV agent into the side feed port 1#, and add the tea fiber into the side feed port 2#; Step three, after setting the processing technology, melt blending, cooling, granulation and drying are carried out to obtain a light-transmitting tea fiber modified polypropylene composite material.
12. The method for preparing a light-transmitting tea fiber-modified polypropylene composite material for automobile interior decoration according to claim 11, characterized in that: The processing temperatures of the I~X zones of the twin-screw extruder involved are 125℃, 155℃, 165℃, 165℃, 170℃, 175℃, 180℃, 185℃, 185℃, 185℃. The main screw speed is 300~450r / min, the water tank temperature is 23℃~50℃, and the melt temperature should be controlled within 200℃; The side feed port 1# should be after the melting section and before the mixing section of the twin-screw extruder to prevent the whiskers from being sheared too much and causing performance degradation; The side feed port 2# should be located after the mixing section and before the metering section of the twin-screw extruder to prevent the tea fibers from being coked at high temperature and causing yellowing in appearance.
Citation Information
Patent Citations
Modified polypropylene material, preparation method thereof and automobile part
CN118085458A
Light-transmitting bumper, vehicle and production process of light-transmitting bumper
CN118478818A
High-light-transmittance and light-weight polypropylene composite material and preparation method thereof
CN111763379A
Reflective polypropylene composite material suitable for automotive trim and preparation method of reflective polypropylene composite material
CN114479287A
Uniform light-transmitting polypropylene composite material as well as preparation method and application thereof
CN115197501A